Analisis Pesan Moral Film Pendek PT Kereta Api Indonesia “Ruang Tunggu” Karya Galih Firdaus: (Analisis Semiotika Charles Sanders Pierce) - Aditya Alif Saputro; Harmonis Harmonis (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Film is a communication medium capable of conveying moral messages to the public through a series of moving images, usually accompanied by sound. One such medium is the short film.